Fast and cost effective fabrication of microlens arrays for enhancing light out-coupling of organic light-emitting diodes - Stellmacher, Andre (2019)
The efficiency of organic light-emitting diodes (OLEDs) deposited on flat substrates is strongly limited by the total internal reflection at the air-substrate interface. An effective strategy to reduce the amount of substrate modes and enhance the light out-coupling into the air is attaching a microlens array (MLA) on the external surface of OLEDs. In this study, polymeric MLA with periods between 1.2 µm and 2.0 µm are patterned by plate-to-plate nano-imprint lithography using metallic stamps structured by direct laser interference patterning. When MLA with a spatial period of 2.0 µm and a structure depth of 200 nm are employed on red, green and blue OLEDs, the external quantum efficiency is increased to 11.4%, 6.6% and 12.7%, respectively, due to a reduction of internally reflected radiation at the air-MLA-glass interfaces.